The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1534/genetics.113.153874
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage and Mutagenesis in Saccharomyces cerevisiae: Genetic Studies of Pathways Affecting Replication Fidelity of 8-Oxoguanine

Abstract: Oxidative damage to DNA constitutes a major threat to the faithful replication of DNA in all organisms and it is therefore important to understand the various mechanisms that are responsible for repair of such damage and the consequences of unrepaired damage. In these experiments, we make use of a reporter system in Saccharomyces cerevisiae that can measure the specific increase of each type of base pair mutation by measuring reversion to a Trp+ phenotype. We demonstrate that increased oxidative damage due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 89 publications
(139 reference statements)
0
15
0
Order By: Relevance
“…In addition to damaged bases, it has also been shown that MMR can target mispairs involving ribonucleotides [18]. We also demonstrated that when endogenous levels of reactive oxygen species were increased by elimination of Sod1, base pair mutation rates generally increased by an order of magnitude or more in the absence of MMR [13]. A recent genome-wide analysis of spontaneous mutations in E. coli showed a 100-fold increase in base pair substitutions in MMR-defective compared to wild type strains [19].…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…In addition to damaged bases, it has also been shown that MMR can target mispairs involving ribonucleotides [18]. We also demonstrated that when endogenous levels of reactive oxygen species were increased by elimination of Sod1, base pair mutation rates generally increased by an order of magnitude or more in the absence of MMR [13]. A recent genome-wide analysis of spontaneous mutations in E. coli showed a 100-fold increase in base pair substitutions in MMR-defective compared to wild type strains [19].…”
Section: Introductionmentioning
confidence: 79%
“…As one example, in one set of our trp5 strains, we found that elimination of Ogg1, a glycosylase removing 8-oxoG opposite a C, increased reversion rates by more than an order of magnitude and elimination of MMR in such strains increased reversion rates by an additional order of magnitude (Fig. 4A) [13]. Because all reversion events occurred through the same base pair change at the same locus, the intermediate reversion rates observed in ogg1 strains suggested a partial deficit of MMR activity.…”
Section: Recent Results Demonstrating Non-canonical Effects Of Mmrmentioning
confidence: 99%
See 3 more Smart Citations